Performance of Ardu (Ailanthus excelsa Roxb) under Silvipasture System in Semi-arid Areas of Rajasthan - Meena, L.R.; Mann, J.S.; Sharma, S.C.; Mehta, R.S. (Indian Journal of Agroforestry, 2020)
The increment in growth parameters viz. plant height (m), collar diameter (cm) and canopy diameter (m) of ardu tree was maximum in the lowest density (25 ardu trees/ha). Whereas, dry leaf, fuel wood yield and total biomass production per hectare of ardu tree were recorded higher in 100-ardu trees density. Intercropping of fodder crops with ardu tree resulted positive impact on growth and development of ardu. These parameters were also observed higher with plantation of cenchrus and cowpea in 1:2 ratio. Soil moisture content at 30 cm depth was higher at higher density of ardu i.e. at 100 trees/ha.